Eksistensi Hukum Militer dalam Menjamin Profesionalisme Tentara Nasional Indonesia - Sianturi, Catherine Rosalina; Triadi, Irwan (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Military law is an important part of the national legal system that serves to ensure the professionalism of the Indonesian National Army through discipline, ethics, and distinctive internal law enforcement. The military legal system is regulated by Law No. 31/1997 on Military Justice to meet the different needs of military organizations and civil society, especially with regard to discipline enforcement, hierarchy, and preparedness. However, in its implementation, there are various challenges such as overlapping jurisdictions with the general courts, lack of transparency, and a military culture that opposes democratic principles. There is a need to formulate solutions to the existing structural and normative barriers. Military law reform is needed so that the system can be aligned with human rights and the rule of law, and so that Indonesian National Army remains neutral and integrity as a professional national defense tool